Peningkatan Pemahaman Matematika Siswa SMA Nurul Jadid Melalui Bimbingan Belajar Berbasis Gim Fun Arithmatic - Arini Hidayati; Hullyatul Badi’a; Muhammad Alaika; Nur Kamiliatus Syarifa (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2026)
High school student’s poor understanding of mathematics remains a common problem, particularly in terms of learning motivation and independent problem-solving skills. This situation is also experienced by students at Nurul Jadid High School, where mathematics lessons tend to be perceived as difficult and boring. This community service activity aims to improve student’s mathematical understanding through the implementation of the Fun Arithmetic game-based tutoring program, designed to be interactive and fun. The methods used in this activity include planning, implementation, and evaluation. The activity was implemented through group tutoring using an educational math game that integrates the concepts of counting, problem-solving, and healthy competition between students. Evaluation was carried out through observation, and pre- and post-activity comprehension tests. The results of the activity showed an increase in students' understanding of mathematical concepts, as indicated by an increase in final test scores compared to the initial test. In addition, students demonstrated a more positive, enthusiastic, and active attitude in participating in mathematics learning. Thus, the Fun Arithmetic game-based tutoring program has proven effective as an alternative learning strategy to improve students' mathematical understanding of Nurul Jadid High School and create a more interesting and enjoyable learning atmosphere.